Pyrolytic Carbon and Cobalt-Chromium Bone Liners Flexible Implant Arthropinlasty - McGehee, J. A.; Swanson, A. R.; Braden, T. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
An in vivo evaluation was conducted on the ability of synthetic bone liners to protect the Swanson High Performance Silastic Finger Joints following 73 flexible arthroplasties in the rabbit stifle. Three different groups of synthetic bone liners were tested against a control group in which no bone liners were used. The implanted bone liners consisted of 48 full circumference liners fabricated from pyrolytic carbon, 34 full circumference and 32 partial circumference liners of a cobaltchromium alloy (Vitallium).
Keywords: Silastic; Bone liner; Pyrolytic carbon; Implant arthroplasty; Cobalt-chromium